Keanekaragaman Makroalga di Pantai Mertasari, Sanur, Pulau Bali - Wiguna, Gede Aryanta; Arthana, I Wayan; Dewi, Ayu Putu Wiweka Krisna (Journal of Marine Research and Technology; Vol 8 No 1 (2025): FEBRUARI 2025, 2025)
Mertasari Beach is rich in natural resources such as mangroves, seagrasses, coral reefs, macroalgae, and other aquatic biota. This research aims to determine the composition, coverage, and diversity of macroalgae species, as well as water quality. This research uses a quantitative descriptive method. Sampling was conducted randomly per station. There are 11 species of macroalgae found, with Ulva compressa having a coverage of 14.27%. The macroalgae diversity index is categorized as moderate to low, ranging from 0.0764 to 1.5302. U. compressa also has the highest importance value index at 79.7%. Water quality includes temperatures ranging from 29-31?C, salinity ranging from 30-35ppt, pH ranging from 8-8.43, nitrate ranging from 0.169-0.429mg/L.